Optimisation of moderator and neutron guide design for prompt gamma neutron activation analysis (PGNAA) using MCNP5 simulation - Mohamed Johan, Mazni (2013)
The performance of prompt gamma neutron activation analysis (PGNAA) setup depends on thermal neutron flux available at the sample. Neutrons available in most reactors consist of thermal, epithermal and fast neutrons with varying ratios. As such for PGNAA to be more efficient, the ratio of the total amount o f neutron to the epifast neutron must be high and this is being measured by the cadmium ratios. In order to increase the neutron flux, a moderator is used. In this study, combination of carbon, lead and silicon were modelled as a moderator to investigate the optimum thickness of moderator combination through a simulation technique. The moderator was tested with varying thickness of material assemblies and it was found that the combination of 1.48 cm carbon, 0.92 cm lead and 4.40 cm silicon gave the highest cadmium ratio. The Monte Carlo N-Particle transport code version 5 (MCNP5) and the exact dimension of the tangential beamport of Reactor Triga Puspati, Malaysian Nuclear Agency was used for the simulation purposes. The simulations then were run at seven locations along the tangential beamport in order to determine the position to place the moderator that yield the highest cadmium ratio. The location at 41.10 cm from the inner beamport exit produced 8.914 x 107 n cm'2 s'1 thermal neutron and 1.164 x 107 n cm'2 s '1 epi-fast neutron that yield 8.65 for the cadmium ratio. Consequently, this position could be suggested as the specific position to place the moderators for future PGNAA system at Reactor Triga Puspati. A one meter neutron guide has been proposed to be installed at the end of the moderator to transport the neutron with almost no neutron lost. The study shows that the proportion of thermal neutron lost was approximately 1.13 times